1998
DOI: 10.1076/ejom.36.3.183.4768
|View full text |Cite
|
Sign up to set email alerts
|

Podophyllotoxin-Induced Acantholysis and Cytolysis in a Skin Equivalent Model

Abstract: Skin equivalent models are used for a wide variety of pharmacotoxicological trials. The present study was performed to assess morphologically the effect of podophyllotoxin on human bioengineered skin. The untreated model exhibited many resemblances with the parent tissues, although the epidermal differentiation was slightly impaired at the ultrastructural level. The penetration of podophyllotoxin and its biological effects inside the model appeared largely increased compared to the clinical experience with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies on penetration of PPT into human bioengineered skin have demonstrated that PPT analogs induce acantholysis and cytolysis in this skin‐equivalent model . We reported that PPT derivatives exhibit insecticidal activity against some economically important insects, more promising and pronounced activity as compared with PPT .…”
Section: Biological Activities and Medical Applicationsmentioning
confidence: 84%
“…Studies on penetration of PPT into human bioengineered skin have demonstrated that PPT analogs induce acantholysis and cytolysis in this skin‐equivalent model . We reported that PPT derivatives exhibit insecticidal activity against some economically important insects, more promising and pronounced activity as compared with PPT .…”
Section: Biological Activities and Medical Applicationsmentioning
confidence: 84%
“…The other relies on in vitro models with excised human skin or its alternatives, such as cell cultures, refined bioengineered skin, and epidermal or dermo-epidermal equivalents (6,7). A series of these procedures appears to predict the in vivo outcome, although they react strongly, and probably excessively, in comparison to the in vivo situation (8). As the process of irritation is complex, no single parameter or study endpoint has yet emerged as the ideal predictor of skin irritation.…”
Section: Introductionmentioning
confidence: 99%